Research on the time-varying charging and dynamic data routing strategy for rechargeable wireless sensor networks - Jiang-hong HAN; Xu DING; Lei SHI; Dong HAN; Zhen-chun WEI (Tongxin xuebao)
The energy problem of wireless sensor networks could be solved by recharging sensor nodes periodically through the wireless energy transfer technique,which ld made sensor nodes remain optional persistently.However,appropriate charging and routing strategies were also in great needs.According to the optimization object of maximizing the vacation time ratio of a wireless charging equipment,the continuous time-varying model,the discrete (N+1)-phased nonlinear model and the solvable discrete (N+1)-phased linear model for the charging and routing strategy were proposed successively.The feasibility of these models was proved as well.In conclusion,after solving the last proposed model,the optimized charging and routing strategies were obtained for networks in different scales.